Transient Behaviour of High Impedance Protection Applications using for Networks with Distributed Generation - Jäger, Johann; Braisch, Dieter; Ramold, Mathias; Li, Shang; Krebs, Rainer (2005 IEEE St. Petersburg PowerTech, 2005)
The presented paper is dealing with protection principles which are preferable applied to networks with distributed generation (DG). A basic physical explanation of the high-impedance protection principle in relation to the low-impedance principle will be given considering the transient behaviour in particular. It can be shown that special requirements on the protection co-ordination for networks with DG can be covered by the high-impedance protection principle. Measurement results of a high current lab confirm the favourable behaviour of the high-impedance protection principle. It was also possible to investigate the transient behaviour of the high-impedance principle under extreme conditions like CT remanence effects. A close correlation between digital simulation and measurement results of the transient behaviour could be achieved during the investigations.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.leen.transi
Keywords: Digital simulations; Distributed generation; High-impedance protection; Measurements; Transient behaviour